2021 IEEE/ACM 4th International Workshop on Emerging Trends in Software Engineering for Blockchain (WETSEB) 2021
DOI: 10.1109/wetseb52558.2021.00012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Machine-Learning Techniques for Detecting Smart Ponzi Schemes

Abstract: Ethereum is one of the most popular platforms for exchanging cryptocurrencies as well as the most established for peer to peer programming and smart contracts publishing [3]. The versatility of the Solidity language allows developers to program general-purpose smart contracts. Among the various smart contracts, there may be some fraudulent ones, whose purpose is to steal Ether from the network participants. A notorious example of such cases are Ponzi schemes, i.e. a financial frauds that require investors to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The scam's foundation of the Ponzi scheme is deceit and lies, and it relies on both to deceive innocent investors by encouraging their conviction that they will receive the anticipated rewards 20 . The operator of the Ponzi scheme makes use of the Ethereum platform to achieve their goal 16,21,22 . Ethereum is a decentralized blockchain platform that creates a peer-to-peer network for securely executing and verifying application code known as smart contracts.…”
Section: Related Workmentioning
confidence: 99%
“…The scam's foundation of the Ponzi scheme is deceit and lies, and it relies on both to deceive innocent investors by encouraging their conviction that they will receive the anticipated rewards 20 . The operator of the Ponzi scheme makes use of the Ethereum platform to achieve their goal 16,21,22 . Ethereum is a decentralized blockchain platform that creates a peer-to-peer network for securely executing and verifying application code known as smart contracts.…”
Section: Related Workmentioning
confidence: 99%
“…Ostapowicz and Żbikowski (2019) have compared the capabilities of Support Vector Machines, Random Forest and XGBoost to identify malicious accounts. In Ibba et al (2021), machine learning algorithms are used to classify the smart contracts that are a part of a Ponzi Scheme. The dataset used for training the model consisted of the Ponzi schemes that existed in the Ethereum platform in the years between 2016 and 2018.…”
Section: Literature Surveymentioning
confidence: 99%
“…Boshmaf et al [8] analyse Bitcoin address transactions, found within conversations on Bitcointalk, that are linked to a specific Ponzi scheme. Ibba et al [24] analyse Ethereum smart contracts and use statistical methods to classify 'Ponzi scheme contracts'.…”
Section: Cryptocurrency-related Scamsmentioning
confidence: 99%